2007
DOI: 10.1210/en.2007-1223
|View full text |Cite
|
Sign up to set email alerts
|

Increased P2X7 Receptor Expression and Function in Thyroid Papillary Cancer: A New Potential Marker of the Disease?

Abstract: Nucleotides are increasingly recognized as nonredundant extracellular signals for chemotaxis, cell growth, and cytokine release. Effects of extracellular nucleotides are mediated by P2 receptors, among which the P2X(7) subtype is attracting increasing attention for its involvement in apoptosis, cell growth, and cytokine release. Recent studies showed that P2X(7) is overexpressed in chronic lymphocytic leukemia and breast and prostate cancer. The aim of the present study was to better understand the clinical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 31 publications
7
102
0
Order By: Relevance
“…Surprisingly, it was found that P2X 7 R is expressed at very high levels in several tumours, compared with Deli et al, 2007;Solini et al, 2008) and was even proposed to represent an early cancer marker (Slater et al, 2005). In fact, among all cancer types tested, cervical cancer is the only exception to our knowledge with a decreased expression of P2X 7 R in cancer cells (Li et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Surprisingly, it was found that P2X 7 R is expressed at very high levels in several tumours, compared with Deli et al, 2007;Solini et al, 2008) and was even proposed to represent an early cancer marker (Slater et al, 2005). In fact, among all cancer types tested, cervical cancer is the only exception to our knowledge with a decreased expression of P2X 7 R in cancer cells (Li et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Among the members of the P2X receptors family, the latest cloned P2X 7 receptors (P2X 7 R) (Rassendren et al, 1997) are very unique by different features, some of them are: (1) their sensitivity to ATP (North, 2002), (2) their facilitation under successive or sustained applications of agonist (Hibell et al, 2000;Roger et al, 2008Roger et al, , 2010a and (3) the appearance of a large, non-selective membrane pore after sustained stimulations with ATP (Pelegrin and Surprenant, 2006). Recently, several tumours have been shown to express P2X 7 R at unusually high levels (Adinolfi et al, 2002;Zhang et al, 2004;Slater et al, 2004a, b;Wang et al, 2004a;Raffaghello et al, 2006;Deli et al, 2007;Solini et al, 2008), however, their functionality and involvement in the physiology of cancer cells remain unclear. In some studies performed on breast and prostate cancers, it was suggested that P2X 7 R might be non-functional (Slater et al, 2004a, b), but proposed to serve as an early marker for cancer (Slater et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it can be an anti‐tumour receptor inducing cancer cell death 16, 17. Second, P2X7R can also be a procancer receptor, as it supports cancer cell proliferation, migration and invasion, both in vitro 18, 19 and in vivo 20. One explanation is that these seemingly opposite effects depend on expression/interaction of presumed proapoptotic P2X7A isoform and trophic isoform P2X7B 21.…”
Section: Introductionmentioning
confidence: 99%
“…P2 receptors are also expressed in many types of cancer [9]. Among these molecules, P2X7 receptor shows increased expression in many types of cancer cells [10][11][12][13][14]. Furthermore, activation of P2X7 receptor has been implicated in tumor growth, as well as tumor angiogenesis and metastasis of breast cancer [6, 10-12, 15, 16].…”
Section: Introductionmentioning
confidence: 99%